National Health Service Principles as Experienced by Vulnerable London Migrants in "Austerity Britain": A Qualitative Study of Rights, Entitlements, and Civil-Society Advocacy - Elham Rafighi; Shoba Poduval; Helena Legido-Quigley; Natasha Howard (Kerman University of Medical Sciences, 2016)
Background: Recent British National Health Service (NHS) reforms, in response to austerity and alleged 'health tourism,' could impose additional barriers to healthcare access for non-European Economic Area (EEA) migrants. This study explores policy reform challenges and implications, using excerpts from the perspectives of non-EEA migrants and health advocates in London. Methods: A qualitative study design was selected. Data were collected through document review and 22 indepth interviews with non-EEA migrants and civil-society organisation representatives. Data were analysed thematically using the NHS principles. Results: The experiences of those 'vulnerable migrants' (ie, defined as adult non-EEA asylum-seekers, refugees, undocumented, low-skilled, and trafficked migrants susceptible to marginalised healthcare access) able to access health services were positive, with healthcare professionals generally demonstrating caring attitudes. However, general confusion existed about entitlements due to recent NHS changes, controversy over 'health tourism,' and challenges registering for health services or accessing secondary facilities. Factors requiring greater clarity or improvement included accessibility, communication, and clarity on general practitioner (GP) responsibilities and migrant entitlements. Conclusion: Legislation to restrict access to healthcare based on immigration status could further compromise the health of vulnerable individuals in Britain. This study highlights current challenges in health services policy and practice and the role of non-governmental organizations (NGOs) in healthcare advocacy (eg, helping the voices of the most vulnerable reach policy-makers). Thus, it contributes to broadening national discussions and enabling more nuanced interpretation of ongoing global debates on immigration and health.